Business Models for Sustainability (Ökologisches Wirtschaften - Fachzeitschrift, 2021)
Mining is known to cause high ecological and social impacts. Thus, it has a paramount role in terms of supporting sustainable development, especially in developing or emerging economies. How can sustainability-oriented business model innovations redefine the raw materials sector and improve the sustainability performance?